2021
DOI: 10.1182/blood-2021-149225
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Asciminib (ABL001) in Combination with Dasatinib and Prednisone for BCR-ABL1-Positive ALL in Adults

Abstract: Introduction Oral tyrosine kinase inhibitors (TKIs) that inhibit the constitutively active ABL1 kinase have improved outcomes for BCR-ABL1+ acute lymphoblastic leukemia (ALL) and decreased reliance on cytotoxic chemotherapy (ctx). Later generation, more potent TKIs such as dasatinib (DAS) are particularly effective (Foa et al. Blood 2011; Foa et al. N Eng J Med 2020). ABL001 (asciminib) is a STAMP (Specifically Targeting the ABL Myristoyl Pocket) allosteric inhibitor of ABL1 that binds to a site spatially dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…All patients (10/10) obtained CR after one month of treatment. After 3 months of treatment, all evaluable patients (7/7) remained in CR and 71% of them had a BCR-ABL 3-log reduction [ 152 ]. Preclinical data support the combination of asciminib and ponatinib and one case report has illustrated its feasibility [ 153 , 154 ].…”
Section: Treatment Of Relapsed/refractory Ph+ All Patientsmentioning
confidence: 99%
“…All patients (10/10) obtained CR after one month of treatment. After 3 months of treatment, all evaluable patients (7/7) remained in CR and 71% of them had a BCR-ABL 3-log reduction [ 152 ]. Preclinical data support the combination of asciminib and ponatinib and one case report has illustrated its feasibility [ 153 , 154 ].…”
Section: Treatment Of Relapsed/refractory Ph+ All Patientsmentioning
confidence: 99%
“…These data indicate the potential relevance of using an ATP-competitive inhibitor in combination with asciminib to reduce the emergence of BCR::ABL1 mutations. Studies have already found that combination treatment with other TKIs has higher efficacy than single-agent treatment [47][48][49][50]. In vitro studies found that primary CML patient cells treated with asciminib and ponatinib demonstrated decreased BCR::ABL1 activity and colony formation compared with asciminib monotherapy [47].…”
Section: Bcr::abl1 Kinase Domain Mutations and Their Role In Drug Res...mentioning
confidence: 99%
“…The phase I study also had a treatment arm for relapsed/refractory Ph + ALL patients to be treated with dose escalation of asciminib but the outcome from this patient cohort is yet to be published. There was another phase I study (NCT03595917) investigating the combination of asciminib, dasatinib with prednisolone in Ph + ALL in either the relapsed/refractory or upfront therapy in unfit patients 39 . Asciminib was dosed at either 40, 80 and 160 mg in combination with 140 mg of dasatinib and prednisolone with the primary objective of evaluation for maximum tolerated dose followed by defining the depth and durability of responses 39 .…”
Section: What We Know Regarding the Efficacy Of Asciminibmentioning
confidence: 99%
“…There was another phase I study (NCT03595917) investigating the combination of asciminib, dasatinib with prednisolone in Ph + ALL in either the relapsed/refractory or upfront therapy in unfit patients 39 . Asciminib was dosed at either 40, 80 and 160 mg in combination with 140 mg of dasatinib and prednisolone with the primary objective of evaluation for maximum tolerated dose followed by defining the depth and durability of responses 39 . The primary toxicity was asymptomatic amylase and lipase with preliminary results demonstrating all evaluable patients achieved at least a haematological remission 39 .…”
Section: What We Know Regarding the Efficacy Of Asciminibmentioning
confidence: 99%
See 1 more Smart Citation